TissueEnrich: Tissue-specific gene enrichment analysis - Jain, Ashish (Bioinformatics, 2019)
SUMMARY: RNA-Seq data analysis results in lists of genes that may have a similar function, based on differential gene expression analysis or co-expression network analysis. While tools have been developed to identify biological processes that are enriched in the genes sets, there remains a need for tools that identify enrichment of tissue-specific genes. Therefore, we developed TissueEnrich, a tool that calculates tissue-specific gene enrichment in an input gene set. We demonstrated that TissueEnrich can assign tissue identities to single cell clusters and differentiated embryonic stem cells. AVAILABILITY AND IMPLEMENTATION: The TissueEnrich web application is freely available at http://tissueenrich.gdcb.iastate.edu/. The R package is available through Bioconductor at https://bioconductor.org/packages/TissueEnrich. Both the web application and R package are for non-profit academic use under the MIT license. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.